2023
DOI: 10.5933/jkapd.2023.50.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Color Adjustment Potential of Single-Shade Composite Resin in Primary Teeth

Abstract: Restoring composite resins with the optimal shades for all primary teeth is a great challenge for pediatric dentists. A newly developed single-shade composite resin can exhibit a color similar to that of the surrounding tooth structure based on the structural color phenomenon. This study aims to evaluate the color adjustment potential (CAP) of a single-shade composite resin compared to conventional multi-shade composite resins in primary teeth. A single-shade composite resin and two conventional multi-shade co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Color evaluation results using a spectrophotometer showed that the ΔE ab * value for the control group with the restoration solely done with Omnichroma was 3.20, demonstrating the lowest value and falling within the clinically acceptable range, consistent with previous Omnichroma color matching studies [8,11,22]. The UB and TC groups exhibited higher values of 3.39 and 4.15, respectively, than the control group; however, these differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Color evaluation results using a spectrophotometer showed that the ΔE ab * value for the control group with the restoration solely done with Omnichroma was 3.20, demonstrating the lowest value and falling within the clinically acceptable range, consistent with previous Omnichroma color matching studies [8,11,22]. The UB and TC groups exhibited higher values of 3.39 and 4.15, respectively, than the control group; however, these differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 79%
“…According to previous studies, the clinically acceptable range of ΔE* varies from 3.3 to 3.7. However, in this study, we utilized the widely adopted standard of 3.3, established by the U.S. Public Health Service, for our color difference assessment [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…1 Learning from the nature as to what should be mimicked begins with the creation of databases on the fundamental optical properties of human teeth (permanent and primary) and gingiva. [203][204][205] The FL and…”
Section: Fuzzy Technologies In Biomimetic Color Analysis and Modelingmentioning
confidence: 99%
“…Learning from the nature as to what should be mimicked begins with the creation of databases on the fundamental optical properties of human teeth (permanent and primary) and gingiva 203–205 . The FL and TSK fuzzy system exhibits great potential for approximating color perception in the calculation of color difference thresholds in the realm of dentistry.…”
Section: Fuzzy Logicmentioning
confidence: 99%
“…In addition, there are disadvantages such as long working time, sensitivity to moisture and contamination, as well as polymerization shrinkage, which are more prominent when treating children 4) . In order to prevent polymerization and shrinkage of the composite resin, the layered filling method was used, but when layered filling is performed, there are problems in that the treatment time is prolonged even if the operator is highly skilled, and it is not easy to control moisture and contamination 5) .…”
Section: Introductionmentioning
confidence: 99%